INSENCE COMBUSTIBLE SEREH, CENGKEH DAN JERUK SEBAGAI PENOLAK NYAMUK AEDES AEGYPTI - Sri Mulyani; Budi Mulyaningsih; Anindita Winda Lestari; Fitri Ana Munawaroh; Diescendy Selly Anna (Majalah Obat Tradisional, 2013)
Mosquitoes are one of the insect vector-borne diseases such as dengue, malaria, filariasis, etc. The use of materials whose got repellent activity such as lemongrass, cloves, and orange leaves are one of the best way to be protected from mosquito bites. Combustible insence known as aromatherapy preparations that can be used at any time, which is commonly used in religious events. This research is intended to make preparations of combustible insence which has dual functions, serve as room fresheners and also as repellent against Aedes aegypti. The research is conducted by making preparations of the active ingredient of lemongrass, cloves, and orange leaves, each with 5 different concentrations. Those preparats are tested on 25 mosquitoes contained in double trap mosquito cages. The number of mosquitoes in box A and B will be calculated at 5, 10, 15, 30, 45, and 60 minutes respectively. Thus, the repellent activity can be determined. Chromatogram profile testing is also being conducted using TAS microdestilation metode with several reagents for identification. Result shown that all preparations have mosquito repellent activity with 40% of effective concentration for lemongrass, 20% for orange leaves, 10% for cloves leaves. Chromatogram profile test shows orange leaves have the most spots for terpenoid and fenolic compound, followed by cloves and lemongrass. Spots as compounds with carbonyl groups (aldehydes and ketones) is only found in lemongrass.